Land health surveillance and response: A framework for evidence-informed land management. (January 2015) - Shepherd, Keith D.; Shepherd, Gemma; Walsh, Markus G.
Highlights: There is insufficient specific evidence on land degradation to focus action. Land health problems share many features with public health problems. Scientific principles of public health surveillance are applied to land health. National land health surveillance systems could generate large development benefit. Preventive strategies that reduce distal risks at national levels are needed. Abstract: Degradation of land health – the capacity of land, relative to its potential, to sustain delivery of ecosystem services – is recognized as a major global problem in general terms, but remains poorly quantified, resulting in a lack of specific evidence to focus action. Land health surveillance and response is designed to overcome limitations of current assessment approaches. It is modelled on science principles and approaches used in surveillance in the public health sector, which has a long history of evidence-informed policy and practice. Key elements of the science framework are: (i) repeated measurement of land health and associated risk factors using probability based sampling of well defined populations of sample units; (ii) standardized protocols for data collection to enable statistical analysis of patterns, trends, and associations; (iii) case definitions based on specific diagnostic criteria; (iv) rapid low cost screening tests to permit detection of cases and non-cases in large numbers of samples; (v) cost-effectiveness evaluation of interventions based on projected reduction in risks and problem incidence; (vi) design of statistically analysable studies to evaluate interventions in the real-world; (vii) meta-analysis of these data to guide design of public policy and intervention programmes; and (viii) integrating surveillance and the communication and use of results into operational systems as part of regular policy and practice. The scientific rigour of land health surveillance has potential to provide a sound basis for directing and assessing action to combat land degradation. Specialized national surveillance units should be established to harness and realign existing resources to provide integrated national land health systems. An international unit is needed to provide science and technology support to governments and develop standards, whereas an international agency should coordinate land health surveillance globally. Application of the surveillance framework could result in a shift away from a focus on rehabilitation of severely degraded land towards a preventive approach that focuses more on reducing distal risks at national and regional levels.